Användande av avskjutningsstatistik i förvaltning - Lindberget, Mirja (2009)
In fisheries, there is a long tradition to use catch data when evaluating changes in the stock and effects from harvesting. It is a common practice to use Catch Per Unit Effort (CPUE) as an index of population size, and several studies have investigated the properties of CPUE in relation to population abundance, spatial distribution and efficiency of gear. In research, catch rate on trap-transects is used as an index of abundance for wildlife species but CPUE is rarely applied as a tool in harvest management. In 1993, more than 60 000 km2 of the state managed mountain range in Sweden was opened to the public for small game hunting, under the responsibility of the county administrative boards in Jämtland, Västerbotten and Norrbotten. The total area is now divided into 332 hunting units (median=73 km2) and an internet based system is used to administer licences and reporting bag statistic. Each hunter has to register the results within two weeks after the hunt. If not, he/she will not be allowed a renewed license. Today the return rate is more than 96% and since 2006 there is an unique data base where hunting unit, date, age, nationality, sex and bag are recorded for each hunter. In this study harvest data were analysed separately for three time periods; the first four days of hunting, day five to eight and day sixteen to nineteen to test if harvest in the previous period of four or eight days would reduce subsequent CPUE. Harvest the four first days did not affect CPUE the following four day period, nor did the accumulated harvest the first eight days affect CPUE the third four day period. Density estimates of willow ptarmigan were obtained from ten areas in the southern most hunted part of the Swedish mountain range. There was a significant but weak positive relationship between density and CPUE. I also compared CPUE between different nationalities (Swedish hunters, other Scandinavian hunters and European hunters) and sex. Most hunting was done by Swedish hunters (83%) and other Scandinavians (15%). Europeans were only (2%). Among Swedish hunters, males constituted 93% and shot more ptarmigans per day than females hunters did. Although CPUE does not show a strong relationship with density, harvest statistics can still be used as a “Threshold of Potential Concern” (TPC) to reduce the risk of over-harvesting willow ptarmigan. By using the information of hunter effort as a baseline variable and number of killed ptarmigans as additional information, to monitor any change in hunter success, is a promising tool in harvest management of willow ptarmigan. Especially if the proportion of European hunters increases in the future.